Automatic Daily Medication Reminder Tool Using an IoT-Based ESP532 Sensor (ELKHA : Jurnal Teknik Elektro, 2026)
Patient compliance with medication schedules remains a major challenge, especially for individuals with chronic diseases requiring long-term and routine treatment. Missed or delayed doses frequently occur due to forgetfulness or the absence of monitoring. This study presents the design of an IoT-based daily medication consumption monitoring system using an ESP32 microcontroller. The system integrates a limit switch to detect the opening of a medicine box as an indicator of medication intake, and is supported by an LED, buzzer, and 16×2 LCD for local reminders and status display. An Android application is included for configuring schedules and receiving real-time notifications. A key methodological difference from previous ESP32-based medication reminder studies is that earlier systems rely mainly on time-based alerts without verifying whether the user actually responds. In contrast, the proposed approach employs sensor-based event detection to confirm physical interaction with the medication box, enabling behavioral verification rather than simple reminder delivery. IoT provides an unprecedented approach in the field of instrumentation and measurement, namely enabling instruments to detect, characterize, and analyze physical phenomena continuously and in real time. This allows the system to log actual user compliance in real time via Firebase. System development involves hardware design, Arduino-based ESP32 programming, and HTTP data communication using JSON processing. Experimental results show that the system reliably detects user actions, triggers reminders, and uploads consumption data. The system has been proven to provide timely notifications via LEDs and buzzers with 100% accuracy. Overall, the system offers a more accurate and responsive method for supporting daily medication adherence.